The Female Voice in Novel The Hunger Games (2008) by Suzanne Collins - Elviza Mz; Leni Marlina (Universitas Negeri Padang, 2023)
Voice is a firm sign of self-assurance and authenticity. To inspire young women all across the world as positive role models, it is crucial to address the perspectives of young female. Young female has the power to set their own objectives, make their own decisions, and put their ambitions and decisions into action. Discussions about The Hunger Games novel related to the issue of gender, politics, power and identity. This study aims to determine how the topic of female agency was expressed in Suzanne Collins' novel The Hunger Games (2008). The protagonist character who is making an attempt to overcome injustice, the power domination, and become a great person in the future is referred to as having female voice. The Marxist-feminisim theory put forward by Karl Marx serve as the foundation for this analysis. The theory's application is based on an interpretation of the novel's text and context. The novel's quotation is the source for the information. This study used content analysis and descriptive research methods. The study's findings demonstrate how women's characters shows her voice in Voicing the Injustice System, Voicing the Power Domination and the Artfulness of the Authority